EFFECT OF DEICING SALT ON PERMEABILITY COEFFICIENT OF ASPHALT MIXTURE UNDER FREEZE-THAW CYCLE - Ковальський, Віктор; Мінджун, Го (SWorldJournal, 2023)
The widespread use of deicing salt in road maintenance work not only protects the pavements, but also causes serious damage to it. This paper investigates and analyzes the influence of three different deicing salt solutions under three low-temperature env